2017
DOI: 10.1017/cem.2017.381
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid hyperemesis syndrome presentation to the emergency department: A two-year multicentre retrospective chart review in a major urban area

Abstract: This study suggests that CHS may be an overlooked diagnosis for nausea and vomiting, a factor that can possibly contribute to unnecessary investigations and treatment in the ED. Additionally, this indicates a lack of screening for CHS on ED history, especially in quantifying cannabis use and eliciting associated symptoms of CHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
0
33
0
3
Order By: Relevance
“…Investigators identified 494 cases, 64% females, mean age 31 (±11) years, of whom 19.4% had notations in their charts that they used marijuana, and in this population, 10.4% reported using marijuana > 3 times per week. Of this patient population of frequent marijuana users, 43% had multiple visits to the ED for the same symptoms (nausea and vomiting) [73]. Many of these patients were treated with rehydration (92%), antiemetics (89%), opioids (27%), underwent some type of imaging procedure (19%), were referred to gastroenterology for further examination (8%), or were admitted to the hospital (8%) [73].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators identified 494 cases, 64% females, mean age 31 (±11) years, of whom 19.4% had notations in their charts that they used marijuana, and in this population, 10.4% reported using marijuana > 3 times per week. Of this patient population of frequent marijuana users, 43% had multiple visits to the ED for the same symptoms (nausea and vomiting) [73]. Many of these patients were treated with rehydration (92%), antiemetics (89%), opioids (27%), underwent some type of imaging procedure (19%), were referred to gastroenterology for further examination (8%), or were admitted to the hospital (8%) [73].…”
Section: Resultsmentioning
confidence: 99%
“…Of this patient population of frequent marijuana users, 43% had multiple visits to the ED for the same symptoms (nausea and vomiting) [73]. Many of these patients were treated with rehydration (92%), antiemetics (89%), opioids (27%), underwent some type of imaging procedure (19%), were referred to gastroenterology for further examination (8%), or were admitted to the hospital (8%) [73]. This suggests that CHS is often overlooked as a possible diagnosis and draws attention to the fact that many CHS patients undergo many unnecessary tests, imaging procedures, and even interventions prior to getting an accurate diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, diagnosis is delayed 2141516. In a small case series including eight patients,14 the average number of emergency department visits before diagnosis was 7.1.…”
Section: Why Is It Missed?mentioning
confidence: 95%
“…Cannabis and/or cannabinoid agents have been used to treat chronic non-cancer pain, with a review of 15 of 18 trials demonstrating analgesic effects compared to placebo [2]. Cannabis has also been used to augment treatment for several neurological disorders, including peripheral neuropathy, muscle spasticity from MS, and epilepsy [3,4]. In addition to its antiemetic properties, cannabis consumption creates appetite stimulation and has been used for cachexia as well as conditions such as AIDS, Parkinson's, and Alzheimer's, ALS, inflammatory bowel disease, and migraine/headaches [5,6].…”
Section: Introductionmentioning
confidence: 99%